Natural Product Chemokine Receptor Antagonists: What Mother Nature Has Offered Us? - Yuan, Yunyun (Current Topics in Medicinal Chemistry, 2014)
Natural products are rich sources of structure-diversified, selective, and potent molecules with a variety of biological activities. Among them, nearly forty compounds have been reported to antagonize binding of chemokines to chemokine receptors, or inhibit functions of chemokines on their receptors. This review covers the chemical structures, biological activities, and structure-activity relationships of these natural products as chemokine receptor antagonists. Three compounds which interact with chemokines, or mediate gene expressions/functions of chemokines are also presented. Due to the complexity of the chemokine receptor/chemokine system in regulating various biological processes, development of therapeutic agents targeting this system remains quite challenging. Nevertheless, some of these natural products can serve as valuable tools or leads to further advance the knowledge and research in this area.
Keywords: natural products